An overview of the mammals of the Gila region, New Mexico - Jones, Amanda K.; Liphardt, Schuyler W.; Dunnum, Jonathan L.; Perry, Travis W; Malaney, Jason; Cook, Joseph A (THERYA, 2021)
A study of the mammals of the Gila region of New Mexico was conducted from 2012 through 2020, with 2,919 voucher specimens collected through fieldwork and collaborations with commercial trappers, in addition to data from camera traps, review of major holdings at 46 museums (n = 12,505 georeferenced specimens), and literature review. Specimens cover a 170-year span, dating back to 1850 and were unevenly distributed spatially and temporally across the Gila region. Most areas were very poorly represented and when summed across all mammal species, ranged from 0.02 to 3.7 specimens per km2. The survey documented 108 species (104 now extant) for the region. High species richness, greater than that reported for 38 states in the United States, is likely due to the juxtaposition of multiple biomes in the Gila, including the Sonoran, Chihuahuan, and Great Basin deserts, the Rocky Mountains and Sierra Madre Occidental, and nearby “sky islands’’ of the Southwest. Two species, Leptonycteris yerbabuenae and Zapus luteus, are documented for the first time from the study area. Expansions of the known range of these species, and Sciurus arizonensis are described from specimen and camera data. Preliminary phylogeographic studies of four species (Notiosorex crawfordi, Neotoma albigula, Perognathus flavus, and Thomomys bottae) using the mitochondrial cytochrome-b gene reveal the dynamic biogeographic history of the region and reinforce how landscape complexity and climate change have jointly contributed to diversification and thus high mammalian diversity in the region.